2016
DOI: 10.1093/nar/gkw272
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis and prediction of G-quadruplex forming sequences in double-stranded DNA

Abstract: G-quadruplex (GQ) is a four-stranded DNA structure that can be formed in guanine-rich sequences. GQ structures have been proposed to regulate diverse biological processes including transcription, replication, translation and telomere maintenance. Recent studies have demonstrated the existence of GQ DNA in live mammalian cells and a significant number of potential GQ forming sequences in the human genome. We present a systematic and quantitative analysis of GQ folding propensity on a large set of 438 GQ forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Experiments in yeast systems have shown that smaller loop elements confer greater thermodynamic stability to G4 formation where the exposed loops are prone to mutation (Fig. 1C; Tippana et al 2014;Piazza et al 2015;Kim et al 2016). Indeed, our analysis supports these experiments showing that loops have a ∼1.15to 1.8-fold enrichment in mutagenesis over G-runs ( Fig.…”
Section: Non-b Dna Motifs Are Associated With Increased Mutability Insupporting
confidence: 83%
“…Experiments in yeast systems have shown that smaller loop elements confer greater thermodynamic stability to G4 formation where the exposed loops are prone to mutation (Fig. 1C; Tippana et al 2014;Piazza et al 2015;Kim et al 2016). Indeed, our analysis supports these experiments showing that loops have a ∼1.15to 1.8-fold enrichment in mutagenesis over G-runs ( Fig.…”
Section: Non-b Dna Motifs Are Associated With Increased Mutability Insupporting
confidence: 83%
“…Loops as large as N=30 can support G-quadruplex formation in vitro [15] and most predictive algorithms permit a user-defined loop length. Short loops are, however, a major factor in G-quadruplex stability [16,17] and some algorithms incorporate this, together with other factors, into a sliding score for G-quadruplex propensity and stability, rather than a binary prediction [5,7,18]. The picture is further complicated by recent evidence that 'bulged' G-quadruplexes can occur in vitro (with a non-guanine base interrupting a 3-guanine track sequence) [14,19], and also that two instead of three guanines quartets can suffice, particularly in RNA, giving rise to G2 Nx quadruplexes [20].…”
Section: Predicting G-quadruplexes Using Bioinformatics Methodsmentioning
confidence: 99%
“…A growing body of structural and biophysical data demonstrates that these structures frequently escape the consensus motif (i.e., G n ‐N i ‐G n ‐N j ‐G n ‐N k ‐G n , in which n= 2 to 4; i , j , k =1 to 7; and N=any base), as evidenced by snap‐back, G‐vacant, and bulged G4 structures which are difficult to predict by bioinformatics algorithms . In this context, experimental probing of formation and topology of G4 structures, both in vitro and in the cellular environment, is crucial for understanding of their persistence and biological roles, as well as for improvement of bioinformatics algorithms …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] In this context, experimental probing of formationa nd topology of G4 structures,b othi nv itro and in the cellular environment, is crucial for understanding of their persistence and biological roles, as well as for improvement of bioinformatics algorithms. [15][16][17][18] Along these lines, apromising approach to assess the formation and topology of G4 structures relies on the use of smallmolecule fluorescent "light-up" probes, the emissiono fw hich is triggered by interaction with the substrate. An umber of fluorescentp robes for G4-DNA have been described to date, as summarized in several recentr eviews.…”
Section: Introductionmentioning
confidence: 99%